Officer Clemmons a memoir - Clemmons, François 1945- (Catapult, 2020)
The intimate debut memoir by the man known to the world as Mister Rogers' Neighborhood 's "Officer Clemmons," a Grammy Award-winning artist who made history as the first African American actor to have a recurring role on a children's television program
Keywords: Clemmons, François -- 1945-; Mister Rogers' neighborhood -- Fernsehsendung; Geschichte; Schwarze; Schauspieler; USA; Clemmons, François; Rogers, Fred / Friends and associates; Mister Rogers' neighborhood (Television program); Musicians / Biography; African American musicians / Biography; Gay men / Biography; Rogers, Fred; African American musicians; Friendship; Musicians; African American entertainers / Biography; African American gay men / Biography; Memoirs; Biographies; Autobiographies; Autobiografie